The Effect of People's Business Credit Facility (KUR) and Financial Literacy on the Welfare of MSME Actors with Business Productivity as a Mediation Variable - Tommy Wahyu Pratomo; Veisya Afra Nurprayasha; Sulaeman Rahman Nidar; Sutisna Sutisna (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
Based on data from the Ministry of Cooperatives and SMEs, the Micro, Small and Medium Enterprises (MSMEs) sector in Indonesia reached 64.2 million units and contributed 61.07% to the Gross Domestic Product (GDP). West Java Province ranks first with the largest number of MSMEs, including the Jatinangor area which is experiencing rapid growth of MSMEs along with its development as an educational area. However, most MSME players in this region face obstacles in business development due to low financial literacy and limited access to formal financing, such as the People's Business Credit (KUR). Bank Mandiri, as one of the largest KUR channeling banks, has developed digital innovations and strategic partnerships to increase the financial inclusion of MSME players. This study aims to analyse the effect of KUR facilities and financial literacy on the welfare of MSME actors, with business productivity as a mediating variable. The research method used is quantitative with a Partial Least Square - Structural Equation Modeling (PLS-SEM) approach. Based on the results of the analysis of data obtained from MSME actors in Jatinangor, it was found that KUR and financial literacy have a direct and significant effect on productivity and welfare. In addition, productivity is proven to mediate the relationship between the two variables and welfare. The results of this study suggest that strengthening access to financing and improving financial literacy are key strategies in encouraging the productivity and welfare of MSMEs in a sustainable manner, especially in semi-urban areas such as Jatinangor.